Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 6; b = 11; c = 3


= 6.3 = 18


And either of their sum or difference = b


= 11


Thus the two terms are 9 and 2


Sum = 9 + 2 = 11


Product = 9.2 = 18




3x(2x + 3) + 1(2x + 3) = 0


(3x + 1)(2x + 3) = 0


(3x + 1) = 0 or (2x + 3) = 0


x = (-1)/3 or x = (-3)/2


Roots of equation are ,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics